Physicochemical quality retention of ‘Sucrier’ bananas (Musa acuminata AA group cv. ‘Kluai Khai’) by jicama starch-based postharvest treatment - Chairat Techavuthiporn; Wasetthee Sittiprasert; Hataitip Nimitkeatkai; Pannipa Youryon; Suriyan Supapvanich (Journal of Agriculture and Food Research, 2024)
The objective of this research was to develop a new type of edible coating using jicama starch (JS) in order to control the postharvest deterioration of ‘Sucrier’ bananas ( Musa acuminata AA group cv. ‘Kluai Khai’) during the ripening process in ambient condition (25 ± 1 °C, 85-90 % RH). The preliminary experiment was carried out to investigate the impact of JS concentration (0, 2.5, 5.0, and 7.5 % w/v) on the postharvest quality of bananas. The application of JS demonstrated a delay in banana ripening, including color development, weight loss, and fruit firmness. Within the JS-treated banana groups, 5.0 % treated bananas displayed higher firmness compared to the other groups. Therefore, a validation experiment was conducted to verify the subsequent physicochemical alterations in bananas after subjecting bananas to 5.0 % JS coating in comparison to non-treated bananas during storage at ambient condition. The JS treatment maintained the color and visual appearance by minimizing the formation of malondialdehyde content and electrical conductivity during storage. Furthermore, it resulted in a delay in the increases in total soluble solid, titratable acidity, BrimA, and total carotenoid concentrations in the pulp. Nevertheless, the ascorbic acid and phenolic contents and 2,2-diphenyl-2-picrylhydrazyl scavenging activity of the control samples were likely to be higher than those of the treated bananas, whereas the ferric reducing antioxidant potential of both control and treated bananas showed a comparable trend throughout storage. The outcomes demonstrate that the utilization of JS is an effective approach for improving the overall storage capacity of ‘Sucrier’ bananas. • 5%JS-based coating showed the best maintenance ‘Sucrier’ banana quality. • The JS-based coating inhibits the senescent spots of ‘Sucrier’ banana. • The JS-based coating delays the ripening of ‘Sucrier’ banana. • The JS-based coating enhances the bioactive compounds of ‘Sucrier’ banana. • The membrane strength of the banana peel were preserved by 5 % JS coating.
Keywords: Food composition and properties; Food Science and Nutritional Studies; Botanical Research and Applications